MEASUREMENT OF THE PROTON STRUCTURE-FUNCTION F2 FROM THE 1993 HERA DATA - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Schlereth, J; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1995)
The ZEUS detector has been used to measure the proton structure function F2. During 1993 HERA collided 26.7 GeV electrons on 820 GeV protons. The data sample corresponds to an integrated luminosity of 0.54 pb-1, representing a twenty fold increase in statistics compared to that of 1992. Results are presented for 7